Recent Update on Radiation Dose Assessment for the State-of-the-Art Coronary Computed Tomography Angiography Protocols - Tan, S.; Yeong, C.; Ng, K.; Abdul Aziz, Y.; Sun, Zhonghua (Public Library of Science, 2016)
Objectives: This study aimed to measure the absorbed doses in selected organs for prospectively ECG-triggered coronary computed tomography angiography (CCTA) using five different generations CT scanners in a female adult anthropomorphic phantom and to estimate the effective dose (HE). Materials and Methods: Prospectively ECG-triggered CCTA was performed using five commercially available CT scanners: 64-detector-row single source CT (SSCT), 2 × 32-detector-row-dual source CT (DSCT), 2 × 64-detector-row DSCT and 320-detector-row SSCT scanners. Absorbed doses were measured in 34 organs using pre-calibrated optically stimulated luminescence dosimeters (OSLDs) placed inside a standard female adult anthropomorphic phantom. HE was calculated from the measured organ doses and compared to the HE derived from the air kerma-length product (PKL) using the conversion coefficient of 0.014 mSv_mGy-1_cm-1 for the chest region. Results: Both breasts and lungs received the highest radiation dose during CCTA examination. The highest HE was received from 2 × 32-detector-row DSCT scanner (6.06 ± 0.72 mSv), followed by 64-detector-row SSCT (5.60 ± 0.68 and 5.02 ± 0.73 mSv), 2 × 64-detector-row DSCT (1.88 ± 0.25 mSv) and 320-detector-row SSCT (1.34 ± 0.48 mSv) scanners. HE calculated from the measured organ doses were about 38 to 53% higher than the HE derived from the PKL-to-HE conversion factor. Conclusion: The radiation doses received from a prospectively ECG-triggered CCTA are relatively small and are depending on the scanner technology and imaging protocols. HE as low as 1.34 and 1.88 mSv can be achieved in prospectively ECG-triggered CCTA using 320-detectorrow SSCT and 2 × 64-detector-row DSCT scanners.